2002
DOI: 10.1111/1467-9442.00297
|View full text |Cite
|
Sign up to set email alerts
|

Distributional Effects of Fiscal Consolidation

Abstract: Li4Mih bbb DevwudfwWklv sdshu h{dplqhv wkh glvwulexwlrqdo frqvhtxhqfhv ri sxeolf ghew uhgxfwlrq dfklhyhg wkurxjk vshqglqj fxwv1 Xqghu wkh dvvxpswlrq wkdw sxeolf jrrgv dqg wudqvihuv duh uhodwlyho| pruh ydoxdeoh wr wkh srru/ rxu fdofxodwlrqv lqglfdwh wkdw wkh hoghuo| srru vwdqg wr orvh iurp vxfk srolflhv1 Ghew uhgxfwlrq surgxfhv vkruw0whup ghflwv dqg orqj0whup vxusoxvhv/ dqg zkhq ixwxuh vxusoxvhv duh uhf|fohg lqwr kljkhu surylvlrq ri sxeolf jrrgv dqg wudqvihuv/ ixwxuh jhqhudwlrqv ri srru frxog jdlq1 Li ixwxuh vx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Age can be expected to be of significant importance – young persons may opt for a stronger consolidation such that they do not inherit high debt levels, older persons have been seen as the obstacle to fiscal reform because they will not reap any gains (Jensen and Rutherford, ). Against this conjecture, age exerts no statistically significant influence (neither age individually nor age jointly with age squared)…”
Section: Estimation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Age can be expected to be of significant importance – young persons may opt for a stronger consolidation such that they do not inherit high debt levels, older persons have been seen as the obstacle to fiscal reform because they will not reap any gains (Jensen and Rutherford, ). Against this conjecture, age exerts no statistically significant influence (neither age individually nor age jointly with age squared)…”
Section: Estimation Resultsmentioning
confidence: 99%
“…This specification was chosen on the basis of prior tests which revealed that the impact of household income amounts to a comparison of low versus higher income. any gains (Jensen and Rutherford, 2002). Against this conjecture, age exerts no statistically significant influence (neither age individually nor age jointly with age squared).…”
Section: Self-interest Affects Preferences For Consolidationmentioning
confidence: 89%
See 1 more Smart Citation
“…82 These findings may reflect the 76. See for example Roine et al (2009), Cardoso (1992, Morley (1995), Lopez (2003), or Jensen and Rutherford (2002).…”
mentioning
confidence: 99%
“…As a regular macro model, households, …rms and traders optimise (Samuelson 1947, Sargent 1987) and choose optimal levels of labour supply, employment, consumption, production and trade. Intertemporal optimisation results in the optimal growth rate of output, capital and investment as in Holland and Scott (1998) or Jensen and Rutherford (2002). How can a set of policies be more e¢ cient in terms of welfare to one households rather than to another is evaluated with a social welfare function.…”
Section: Features Of Dynamic Tax Model Of Ukmentioning
confidence: 99%